Behaviourism and attachment theories in the mental health centres in the USA - Bieliauskaitė, R. (Psichologija, 1990)
Experience of organization of mental health centers in the USA is described in this article. W e present here a brief classification of the types of mental health centers and discuss some methodological principles of their organization. Some methods of behavior management are ·described. Application of attachment theory in the Forest Height Lodge is described in detail. Such overview of experience in the USA will help in our own attempts at organizing a mental health center in Lithuania.
Keywords: behaviourism; attachment theory; USA